Modeling and identification of the dynamics of the process of drilling wells on the basis of the catastroph theory - Kropyvnytska, V. B. (Видавництво Львівської політехніки, 2018)
It is proposed to determine the catastrophic deviations of the intensity of the change in drilling time of 1 m rocks in the depth of the well using the model of the catastrophe of the "COLLection" of R.Toma or the model Vapor Pressure. Adjustment of the axial force on the bit according to the developed methodology allows to provide a stable dynamic drilling mode.
Keywords: well-drilling; dynamic stability; chaotic regime; modeling; experimental analysis; 681.5.015; 622.24.085.5